Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 81586 by jagoll last updated on 14/Feb/20

Dear mister   Tanmay  y ′′ − y′ −6y = 2sin 3x   find solution     let y = e^(mx)  ? or not

DearmisterTanmayyy6y=2sin3xfindsolutionlety=emx?ornot

Commented by jagoll last updated on 14/Feb/20

y′ =me^(mx)  ⇒y′′ = m^2  e^(mx)   m^2 e^(mx) −me^x −6e^(mx)  = 0  e^(mx)  (m^2 −m−6)=0  (m−3)(m+2)=0 ⇒m=3 ∧ m=−2  y = Ae^(3x)  + Be^(−2x)

y=memxy=m2emxm2emxmex6emx=0emx(m2m6)=0(m3)(m+2)=0m=3m=2y=Ae3x+Be2x

Commented by jagoll last updated on 14/Feb/20

particular integral   y = ((2sin 3x)/(D^2 −D−6))

particularintegraly=2sin3xD2D6

Commented by TANMAY PANACEA last updated on 14/Feb/20

y=2.((sin3x)/(D^2 −6−D))  =2.(((D^2 −6+D)sin3x)/((D^2 −6)^2 −D^2 ))  =2.(((−9sin3x−6sin3x+3cos3x))/((−3^2 −6)^2 −(−3^2 )))  =(2/(225+9))×((3cos3x−15sin3x)/1)  =(2/(234))×(3cos3x−15sin3x)

y=2.sin3xD26D=2.(D26+D)sin3x(D26)2D2=2.(9sin3x6sin3x+3cos3x)(326)2(32)=2225+9×3cos3x15sin3x1=2234×(3cos3x15sin3x)

Commented by jagoll last updated on 14/Feb/20

sir how to get line 2?

sirhowtogetline2?

Commented by jagoll last updated on 14/Feb/20

oo by multiply  conjugate  (D^2 −6)+D

oobymultiplyconjugate(D26)+D

Commented by TANMAY PANACEA last updated on 14/Feb/20

yes ...objective to multiply by conjuage to get  denominator in terms of D^2

yes...objectivetomultiplybyconjuagetogetdenominatorintermsofD2

Answered by Joel578 last updated on 14/Feb/20

• homogeneous solution with characteristic eq.     λ^2  − λ − 6 = 0 ⇒ λ_1  = −2, λ_2  = 3    ⇒ y_h (x) = C_1 e^(−2x)  + C_2 e^(3x)     • particular solution  y_p (x) = A cos 3x + B sin 3x  y_p ′(x) = −3A sin 3x + 3B cos 3x    y_p ′′(x) = −9A cos 3x − 9B sin 3x  Substitute to the question  (−15A − 3B)cos 3x + (−15B + 3A)sin 3x = 2 sin 3x  ⇒  { ((−15A − 3B = 0)),((−15B + 3A = 2)) :} ⇒  { ((A = (1/(39)))),((B = −(5/(39)))) :}  ⇒ y_p  = (1/(39)) cos 3x − (5/(39)) sin 3x    ∴ y(x) = y_h (x) + y_p (x)                  = C_1  e^(−2x)  + C_2  e^(3x)  + (1/(39)) cos 3x − (5/(39)) sin 3x

homogeneoussolutionwithcharacteristiceq.λ2λ6=0λ1=2,λ2=3yh(x)=C1e2x+C2e3xparticularsolutionyp(x)=Acos3x+Bsin3xyp(x)=3Asin3x+3Bcos3xyp(x)=9Acos3x9Bsin3xSubstitutetothequestion(15A3B)cos3x+(15B+3A)sin3x=2sin3x{15A3B=015B+3A=2{A=139B=539yp=139cos3x539sin3xy(x)=yh(x)+yp(x)=C1e2x+C2e3x+139cos3x539sin3x

Commented by jagoll last updated on 14/Feb/20

thank you mister

thankyoumister

Terms of Service

Privacy Policy

Contact: info@tinkutara.com